Attention retargeting using saliency map and projector–camera system in real space. Issue 6 (19th March 2019) - Takimoto, Hironori; Yamamoto, Katsumi; Kanagawa, Akihiro; Kishihara, Mitsuyoshi; Okubo, Kensuke
Abstract : Many attention‐retargeting methods based on the visual saliency model of bottom‐up attention for guiding human attention to target regions have recently been proposed. However, existing attention‐retargeting methods focus on only modulating an image or a video presented to a display. It is difficult for the existing methods to guide humans' attention to objects in the real space. In this paper, we propose an appearance control method using a projector–camera system to realize attention retargeting in real space. The ideal appearance for attention retargeting is estimated on the basis of reverse engineering of the visual saliency map theory. Our system then projects an optimum light pattern calculated from the difference between the ideal appearance and current appearance in real space. Attention retargeting to the plane of real space is addressed as an initial step of our research. As a result, our attention‐retargeting method can effectively control an appearance in real space for attention retargeting compared with spot light projection. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.